EFEKTIVITAS PROGRAM PENANGANAN KONFLIK SOSIAL DALAM MENCIPTAKAN KONDUSIFITAS DAERAH DI BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN SUMEDANG - Nurwan, Teddy Marliady; Surya, Adit; Firmansyah, Hadi (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to examine the effectiveness of social conflict management programs in creating regional conduciveness in the National Unity and Political Agency of Sumedang Regency, which is an inhibiting factor and an effort to overcome obstacles to social conflict management programs. The method used in the preparation of this research report is the Qualitative Research method. The sampling technique used is Purposive Sampling, which is a sampling technique for data sources with certain considerations. There are 4 people who are used as data sources, namely: Head of National Vigilance, General Administration, Office Administration, Letter or Recap. Meanwhile, in analyzing data, the Miles and Huberman model (sugiyono, 2017:246) is used with step steps: data reduction, data presentation, conclution drawing/verification, and triangulation, as well as data validation. Based on the results of the study, it was concluded that the effectiveness of the social conflict management program in creating regional conduciveness in the National Unity and Political Agency of Sumedang Regency has not been maximized, because there are things that affect so that it becomes an obstacle such as lack of special skills, uneven workload, suggestions and facilities have not been accommodated as a whole. To overcome various things that exist as inhibiting factors, efforts that can be made are to conduct exercises, technical guidance and comparative studies to improve the quality of human resources and improve recommendations and facilities in accordance with the set budget.